Decision support system on quality assessment of the prospective civil servant’s education and training using fuzzy method - Aris Susanto; Omar Wahid; Hazriani Hazriani; Yuyun Yuyun (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
This study aims to develop a decision support system using the fuzzy method in order to assess the quality of education and training of prospective civil servants and highlight possible improvement considerations. The assessment consists of six criterias, namely coaches, lecturers, preachers, mentors, examiners, and administrators. Based on the evaluation result of the quality level of each criterion, it is obtained that the top two criterion are examiners and preachers, followed by coaches, lecturers, advisors, and the lowest is organizer. In addition, the quality of the civil servant class III training is better than the class II civil servant training. It also shows that the value of the organizers criterion has different level of satisfactions. Overall, the quality of the training (according to the participants' opinion) was very good with a score of 92.50 for training class II and 95.20 for training class III. Furthermore, it is necessary to conduct research to determine the quality of the training each year by looking at the achievements of the participants. The >system testing obtained an accuracy of 100%, whichs implies that the system can be used to assess the quality of education and training appropriately.